2016
DOI: 10.1002/mma.4089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of awareness program and delay in the epidemic outbreak

Abstract: In the present paper, an epidemic model has been proposed and analyzed to investigate the impact of awareness program and reporting delay in the epidemic outbreak. Awareness programs induce behavioral changes within the population, and divide the susceptible class into two subclasses, aware susceptible and unaware susceptible. The existence and the stability criteria of the equilibrium points are obtained in terms of the basic reproduction number. Considering time delay as the bifurcating parameter, the Hopf b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…It is easy to show hat if d < 0, then the equation (29) has at least one positive real root. Using the fact that β(M ) is a positive decreasing function, we have…”
Section: A2mentioning
confidence: 99%
See 2 more Smart Citations
“…It is easy to show hat if d < 0, then the equation (29) has at least one positive real root. Using the fact that β(M ) is a positive decreasing function, we have…”
Section: A2mentioning
confidence: 99%
“…It is to be noted that all the previous simulations were considered in the absence of delay (τ = 0) and we can check that with the chosen set of parameters, the condition of the stability of the positive equilibrium E * cited in the theorem 3.5 holds. Now, to investigate numerically the effect of the delay in reporting the infected cases, we treat the roots of the equation (29). It is found that it admits exactly one positive real root 1.9321e −04 , which gives that the characteristic equation (25) has a pair of purely imaginary roots ±0.0139i, and the critical value of the delay is found to be τ 0 = 79.9.…”
Section: Stability and Direction Of The Hopf-bifurcationmentioning
confidence: 99%
See 1 more Smart Citation
“…Time delay occurs often in almost every biological situation. Therefore, investigation of any ecological/epidemiological system without time delay is not realistic [23][24][25][26][27][28][29][30][31] . Detailed topics on the use of time delays in real models can be found in the classical books [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…38 It is noted that there was a big campaign from media on the Ebola epidemic of 2014-2015 in West Africa, but this did not stop the epidemic and death toll due to the breakdowns and cuts in public health infrastructure. 39,40 For some infectious diseases, mathematical models are also studied to see how the delay in implementing awareness programs impacts the dynamics of infectious disease, [41][42][43] and it is observed that incorporation of time delay in the modeling process destabilizes the system. Recently, Agaba et al 44 have studied an SIS-type delay mathematical model by considering local awareness arising from direct interaction between unaware and aware individuals and global awareness originating from public information campaigns.…”
Section: Introductionmentioning
confidence: 99%